PENGARUH LAMA PERENDAMAN DALAM GIBERELIN (GA3) TERHADAP PERKECAMBAHAN BENIH AREN (Arenga pinnata Merr) - Farida Farida (Jurnal Magrobis, 2017)
Research of effect to water long in giberelin acid to germination seed of sugar palm (Arenga pinnata Merr). The research purpose to knowing effect of long time to water I giberelin acid germination seed of sugar palm, and to knowing long time to water giberelin acid of the best for germination seeds sugar palm. Experiment were hold in Sangatta, East Kutai on November 2016 to January 2017 period. The experiments was conducted in non factorial experiments on Completely Randominazed Design (CRD) with four replications. long time on thw water giberelin acid factor is L0 = no application L1 = 5 minutes, L2 = 10 minutes, L3 = 15 minutes, L4 = 20 minutes, L5= 25 minutes, L6= 30 minutes. The result was long time the water of giberelin acid is showed highly significatly on germination percentase, time germination, and index vigor are 82,50%, 46,76 days, dan 0,158.Keyword : Aren, Dormansi, Giberelin.